1979
DOI: 10.1111/j.1365-2125.1979.tb01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of propranolol and metoprolol in the management of hyperthyroidism.

Abstract: 1 Propranolol and metoprolol were both effective in controlling the symptoms and signs of hyperthyroidism. 2 Propranolol caused a highly significant increase in serum reverse T3 concentrations with lesser changes in other serum thyroid hormone levels, whereas metoprolol did not have this effect. 3 Steady‐state plasma propranolol and metoprolol levels showed marked inter‐individual variation. Metoprolol concentrations showed relatively little intra‐individual variability, and could be related to the clinical ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 29 publications
6
31
1
Order By: Relevance
“…The possibility of an important effect of catecholamines on extrathyroidal conversion of T4 to T3 was suggested by clinical studies where -receptor antagonists decreased the plasma concentration of T3 in thyrotoxic or hypothyroid patients maintained on a fixed dose of T4 (Murchison et al 1979, Sulkin et al 1984. Subsequently, in vitro studies in liver and kidney demonstrated that D1 inhibitory effects of propranolol were related to its lipid solubility and not to its -adrenergic blocking activity (Heyma et al 1978, Sulkin et al 1984.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of an important effect of catecholamines on extrathyroidal conversion of T4 to T3 was suggested by clinical studies where -receptor antagonists decreased the plasma concentration of T3 in thyrotoxic or hypothyroid patients maintained on a fixed dose of T4 (Murchison et al 1979, Sulkin et al 1984. Subsequently, in vitro studies in liver and kidney demonstrated that D1 inhibitory effects of propranolol were related to its lipid solubility and not to its -adrenergic blocking activity (Heyma et al 1978, Sulkin et al 1984.…”
Section: Discussionmentioning
confidence: 99%
“…It has been amply confirmed that propranolol causes a significant reduction in serum T3 and a concomitant increase in serum rT3 (Verhoeven et al 1977; Kallner et al 1978;Saunders et al 1978), although its effect on thyroxine is less consistent (Kallner et al 1978;Murchison et al 1979). It was reported that propranolol has no direct effect on thyroid functions, as measured by radioiodine uptake and serum protein-bound-iodine (Wartofsky et al 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors (Heyma et al 1980;Nilsson et al 1980) suggest that propranolol-induced changes in T3 and rT3 concentrations might be due to MSA (Heyma et al 1980) or direct inhibition of the enzyme responsible for the T4 monodeiodionation to T3 (Nilsson et al 1980). It is also possible that the changes might result from f32-adrenoreceptor blockade, since some authors have noticed a decrease in T3 during propranolol treatment, but no changes during the administration of selective f31-adrenoreceptor blockers such as atenolol (Nilsson et al 1979), practolol (Murchison et al 1976), and metoprolol (Murchison et al 1979; Nilsson et al TABLE 3. Pharmacological properties and effect on serum thyroid hormones of carteolol, indenolol and metoprolol 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Peden in 1982 41 reported the use of daily nadolol and being adequately assessed prior to the commencement of surgery. This is important as there is large individual variability in response to propranolol 40,41,51 . Therefore, targets of heart rates <90 beats per minute and absence of symptomatic thyrotoxicosis should be used as end points prior to proceeding to surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Difficulties surrounding the use of propranolol led to a number of studies of other beta-blockers, in particular, more cardioselective agents such as metoprolol 4 . In a doubleblind crossover trial by Murchison in 1979, 51 each patient received 4 weeks of treatment with propranolol and 4 weeks with metoprolol. All showed improvement in clinical symptoms and signs.…”
Section: Resultsmentioning
confidence: 99%